Diurnal course of cloud cover in Poland in the following decades of the year (based on years 1990-2000) - Monika Okoniewska (Kazimierz Wielki University, 2017)
The paper presents the analysis of the course of diurnal cloud cover in Poland. To characterize the nephological conditions selected data from 6 stations: Koszalin, Bialystok, Poznan, Warsaw, Wroclaw and Rzeszow, including the cloud cover of eight observational terms from 1990-2000. The data were averaged over 36 decades of the year. Based on the data the average course of diurnal cloud cover, the annual course of  occurrence of maximum and minimum values and the amplitude of diurnal cloudiness were estimated. The conducted analysis confirmed the decrease in cloudiness in the summer and its growth in the autumn-winter period. Moreover, in winter there was much less variation diurnal cloud cover than in summer. Lowest cloudiness during the year occurred in the summer at night, when it settled at the level of 30-40%, and the minimum daily appeared generally between the hours of 10 p.m. and midnight. The highest values of cloudiness was observed from mid-November to mid-December, especially between 6 am and noon, when it increased significantly above 70%.